Behaviour of an instrumented anthropomorphic dummy during full scale drop tests - Petrone, N.; Panizzolo, F.; Marcolin, G. (Procedia Engineering, 2011)
The aim of this work was to study the behaviour of an instrumented anthropomorphic dummy during full scale drop tests. The dummy presented triaxial accelerometers at head and chest and multiaxial load cells at the thighs. Drops were performed on a wooden floor inclined at 16° from horizontal. Kinematics of drop landing in sagittal plane was filmed with a high speed camera. Peak values of acceleration and thigh loads were recorded to provide a validation of a numerical model of the dummy including stiffness properties of the skis and boots.